Mail and internet surveys : the tailored design method, with new internet, visual and mixed-mode guide - Dillman, Don A (Wiley, 2015)
A guide for creating and conducting successful surveys using both traditional and media channels. It features the developments in online survey design and administration. Drawing on social science, statistics, and proven best practices, it discusses surveys for a variety of purposes, audiences, and situations.